Resonance of Gravitational Axion-Like Particles - Gamboa-Rios, J; Mendez-Ferrada, F (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The motion of gravitational axion-like particles (ALPs) around a Kerr black hole is analyzed, paying attention to the resonance and distribution of spectral radiation. We first discuss the computation of (Formula presented.) and its implications with Pontryagin’s theorem, and then a detailed analysis of Teukolsky’s master equation is carried out. After carefully analyzing the Teukolsky master equation, we show that this system exhibits resonance when (Formula presented.), where (Formula presented.) is the mass of the ALP, while the homogeneous part of the solution exhibits the superradiance. A skew-normal distribution can approximate the energy distribution of the resonant modes, and we give explicit expressions for its lifetime. © 2024 by the authors.